Comparison between self‐formulation and compounded‐formulation dexamethasone mouth rinse for oral lichen planus: a pilot, randomized, cross‐over trial. Issue 3 (26th June 2016) - Hambly, Jessica L.; Haywood, Alison; Hattingh, Laetitia; Nair, Raj G.
Abstract: Aim: There is a lack of appropriate, commercially‐available topical corticosteroid formulations for use in oral lichen planus (OLP) and oral lichenoid reaction. Current therapy includes crushing a dexamethasone tablet and mixing it with water for use as a mouth rinse. This formulation is unpleasant esthetically and to use in the mouth, as it is a bitter and gritty suspension, resulting in poor compliance. Thus, the present study was designed to formulate and pilot an effective, esthetically‐pleasing formulation. Methods: A single‐blinded, cross‐over trial was designed with two treatment arms. Patients were monitored for 7 weeks. Quantitative and qualitative data was assessed using VAS, numeric pain scales, the Treatment Satisfaction Questionnaire for Medication‐9, and thematic analysis to determine primary patient‐reported outcomes, including satisfaction, compliance, quality of life, and symptom relief. Results: Nine patients completed the pilot trial. Data analysis revealed the new compounded formulation to be superior to existing therapy due to its convenience, positive contribution to compliance, patient‐perceived faster onset of action, and improved symptom relief. Conclusion: Topical dexamethasone is useful in the treatment of OLP. When carefully formulated into a compounded mouth rinse, it improves patient outcomes.